Molecular Analysis of Predator Scats Reveals Role of Salps in Temperate Inshore Food Webs - Cavallo, Catherine; Chiaradia, André; Deagle, Bruce E.; McInnes, Julie C.; Sánchez, Sonia; Hays, Graeme C.; Reina, Richard D. (Frontiers in Marine Science, 2018)
High precision, high coverage DNA-based diet analysis tools allow greater insight into the food web interactions of cryptic taxa. We used DNA faecal-metabarcoding to look for unrecorded taxa within the diet of a generalist centrally-placed predator, the little penguin Eudyptula minor. We examined 208 scats from 106 breeding pairs throughout August-February in a large colony at Phillip Island, Australia. While we confirmed a largely piscivorous diet, we also recovered DNA sequences from gelatinous and crustaceous plankton groups that have not previously been detected in the little penguin diet using other diet analysis methods. Gelatinous plankton, including salps, appendicularians, scyphozoans and hydrozoans were present in 76 % of samples and represented 25 % of all sequences. DNA recovered from minute copepods and appendicularians may indicate links between trophic levels through secondary predation. Percentage Frequency of Occurrence (%FOO) demonstrated that little penguin diet composition changed over months and stages (incubation, guard and post guard) of the breeding season (month: χ2 = 201.91, df = NA, p < 0.01; stage: χ2 = 33.221, df = NA, p = 0.015). Relative Read Abundance (RRA) uncovered variations in the relative abundance of taxa in the diet over months and stages (month: F = 53.18, df = 59, p < 0.001; stage: F = 66.56, df = 29, p < 0.001). The diet became progressively fish-focussed over months of the season and stages, while salps were only present in four out of six months, with a peak in September. Based on their prevalence in this dataset, in this year of very high breeding success (2.15 chicks per pair), salps may constitute a food source for this largely piscivorous generalist. Our work highlights how DNA metabarcoding can improve our understanding of the trophic role of gelatinous plankton and other cryptic taxa.